Personal conceptions of intelligence, self-esteem, and school achievement in Italian and Portuguese students - Annamaria Pepi (2006)
Educational research places emphasis on the fact that different cultures have different self-construals. These construals can influence cognitive, emotional, and motivational processes in individuals. Great importance is attached to individuals' implicit conceptions of the nature of their intelligence (incremental or entity) and self-esteem. In general, both representation of intelligence and self-esteem seem to play an important role in scholastic performance in terms of both a predispostion to learning and the results actually achieved. The aim of this research is to determine the relationship between variables such as school, and socioeconomic level and gender in Italian and Portuguese students. A questionnaire was administered to 1,540 high school and university students assessing socioeconomic level and school performance, the Personal Conceptions of Intelligence Test (Faira & Fontaine, 1997), and the Self-Esteem Test (Rosenberg, 1965). In general, results show that Portuguese subjects are more incremental than Italians. Moreover, significant differences have to be determined regarding motivational factors linked to school and socioeconomic level and gender. The research highlights the importance of macro-contextual factors in the social, economic, and political organizations that influence how people develop their motivational beliefs.